Peningkatan Motivasi Membaca dan Menulis Melalui Model PBL di SDI Al Azhar 32 Padang: Increasing Reading and Writing Motivation Through the PBL Model at SDI Al Azhar 32 Padang - Melia Mardi; Frida Nur Lestari; Desmimi Eka Putri; Yasmanelly Yasmanelly; Hasnul Fikri; Syofiani Syofiani (ITScience (Information Technology and Science), 2025)
By using the Problem-Based Learning (PBL) approach at Al Azhar 32 Islamic Elementary School in Padang, this study aims to improve students' reading and writing interest. Learning motivation is crucial to improving students' academic achievement, especially in basic literacy skills such as reading and writing. However, due to the lack of diverse and non-contextual teaching strategies, elementary school students often have low literacy motivation. The PBL paradigm, which focuses on solving real-world problems, is one of the creative, more dynamic, and challenging learning methodologies needed. The Classroom Action Research (CAR) method uses two cycles. Each cycle consists of planning, action implementation, observation, and reflection. The research subjects were fourth-grade students, and a learning motivation questionnaire was administered before and after the activity, along with observations of learning activities and interviews with teachers and students. Descriptive, qualitative, and quantitative analyses were conducted on the data. The research findings indicate that using the PBL paradigm significantly increased children's motivation to write and read. Students' enthusiasm increases, they participate more actively in class discussions, can express their thoughts more systematically, and become interested in literacy-related activities. The Problem-Based Learning approach has increased elementary school students' reading motivation. Through problem-based learning that can be applied to students' daily lives, this approach encourages emotional and cognitive engagement.